Keselarasan Strategik – Pembelajaran Dari Studi-Pilot - Wahyuni Reksoatmodjo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Information technology is an important investment. Rapid development with varying specifications, huge prices but obsolete technologies, forces managers to be prudent in acquiring. This study aims to explore the characteristics of IT infrastruktur that contribute to the achievement of strategic alignment, a concept that enabling the enhancement of company's sustainable competitive advantage. Through a combination of quantitative/quali-tative research methods and pilot-study approach, the study explores the characteristics of the case company's IT infrastructure. Results of the study is an indepth of the characteristics of a flexible IT infrastructure to a company engaged in the business of communication.